PERAMALAN HARGA TERNAK SAPI BERDASARKAN INDEKS PERUBAHAN HARGA - Rusdianto, Sasongko W (Informatika Pertanian, 2014)
Cattle prices in Nusa Tenggara Barat tend to change in short time. It is difficult for farmers to predict price in the future. Price changes could affect farmers income. Therefore we need a method by which farmers could predict the price in order to make production decision. The purpose of this study was to predict of price based on the average price level for one year. This study used secondary data of cattle prices monthly, patterns of changes measured by index, then performed statistical analysis. The results of this study shows that the forecasting method used is only relevant to the pattern of price changes with a relatively similar pattern in a specified period. Price changes caused by external factors will have different pattern and causes greater deviation, so it can not be used to predict the price of cattles in NTB.